2020
DOI: 10.1177/2380084420927326
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Concentrate Treatments for Temporomandibular Disorders: A Systematic Review and Meta-analysis

Abstract: Objectives: This systematic review compared platelet concentrates (PCs) versus hyaluronic acid (HA) or saline/Ringer’s solution injections as treatments of temporomandibular osteoarthritis and disc displacement in terms of pain and maximum mouth opening (MMO). Methods: PubMed, Cochrane, and Scopus were searched up to March 6, 2020. Inclusion criteria were randomized clinical trials (RCTs). Exclusion criteria were case series, observational studies, animal studies, and reviews. The Effective Public Health Pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 43 publications
1
26
0
2
Order By: Relevance
“…There are many known complications of steroid administration, including edema, hypoaesthesia, skin hypopogmentation and even skin atrophy [16,17]. In recent years, injections of platelet-rich plasma (PRP) into the TMJ cavities have become popular and found to be effective [7,[18][19][20][21][22]. Apart from autologous PRP, other self-derived blood products are also used: plasma rich in growth factors (PRGF) and injectable platelet-rich fibrin (I-PRF) [7,23].…”
Section: Introductionmentioning
confidence: 99%
“…There are many known complications of steroid administration, including edema, hypoaesthesia, skin hypopogmentation and even skin atrophy [16,17]. In recent years, injections of platelet-rich plasma (PRP) into the TMJ cavities have become popular and found to be effective [7,[18][19][20][21][22]. Apart from autologous PRP, other self-derived blood products are also used: plasma rich in growth factors (PRGF) and injectable platelet-rich fibrin (I-PRF) [7,23].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to MMO there was no significant difference between PRP and control group. Al-Hamed et al 17 in their meta-analysis showed significant reduction in pain scores with PCs and increase in mouth opening. PCs cause immunomodulation.…”
Section: Discussionmentioning
confidence: 94%
“…PRP is an autologous concentrate of platelets and growth factors, derived from centrifugated blood [ 52 , 53 , 54 ]. There have been listed in the literature two other types of platelet concentrates, namely platelet-rich fibrin (PRF) and plasma rich in growth factors (PRGF) [ 55 ]. PRP may be obtained only from the liquid blood.…”
Section: Resultsmentioning
confidence: 99%